2018
DOI: 10.1038/s41598-018-30688-z
|View full text |Cite
|
Sign up to set email alerts
|

Corneal confocal microscopy detects corneal nerve damage and increased dendritic cells in Fabry disease

Abstract: Fabry disease is characterised by neuropathic pain and accelerated vascular disease. This study evaluates the utility of corneal confocal microscopy (CCM) to non-invasively quantify corneal nerve and endothelial cell morphology and dendritic cell (DC) density in relation to disease severity in subjects with Fabry disease. Seventeen consecutive participants with Fabry disease and 17 healthy control subjects were included in this cross-sectional study. Fabry disease severity was measured using the Mainz Severity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 52 publications
2
42
0
Order By: Relevance
“…Corneal nerve loss has been demonstrated in a cohort of patients with transthyretin familial amyloid neuropathy 23 that was related to the severity of somatic and autonomic neuropathy, but most importantly the nerve loss could be quantified in all of the patients, avoiding the floor effect seen with sural nerve action potential and intra-epidermal nerve fiber density. More recently, we have identified corneal nerve loss in patients with Fabry disease, 24 Friedreich's ataxia, 19 and sarcoidosis 25 and have found significant correlations with neurological disability.…”
Section: Introductionmentioning
confidence: 96%
“…Corneal nerve loss has been demonstrated in a cohort of patients with transthyretin familial amyloid neuropathy 23 that was related to the severity of somatic and autonomic neuropathy, but most importantly the nerve loss could be quantified in all of the patients, avoiding the floor effect seen with sural nerve action potential and intra-epidermal nerve fiber density. More recently, we have identified corneal nerve loss in patients with Fabry disease, 24 Friedreich's ataxia, 19 and sarcoidosis 25 and have found significant correlations with neurological disability.…”
Section: Introductionmentioning
confidence: 96%
“…In different animal models, similar abnormalities of sensory and autonomic functions have been observed after genetic deletion of the α-galactosidase gene [28][29][30]. Prominent morphological changes of the affected thin myelinated and unmyelinated sensory axons are the reduction of the intraepidermal fiber density in the skin [31][32][33] and reduction in the density and length of corneal nerve fibers [32,34]. Swelling of the dorsal root ganglion neurons and accumulation of Gb3 in the cytoplasm of these cells were also reported in human autopsy samples [35,36] and in α-galactosidase knock out animals [28,29].…”
Section: Human Diseases Affecting Glycosphingolipid Metabolism and Painmentioning
confidence: 78%
“…In human sural nerve biopsy material ultrastructural morphometric analysis showed a reduction of the number of both small diameter myelinated axons and unmyelinated axons [36] and appearance of regenerating clusters was also reported [36,37]. Although numerous studies described alterations in the heat or cold thresholds of cutaneous sensory nerves [38,39] and the reduced mechanical sensitivity of the cornea [32,34], observations reporting the specific impairment of chemosensitive C-fiber neurons is sparse. One research group described a reduced flare reaction of the skin induced by subcutaneous administration of capsaicin in patients with Fabry disease [31,40].…”
Section: Human Diseases Affecting Glycosphingolipid Metabolism and Painmentioning
confidence: 99%
“…We have previously used CCM to show loss of corneal nerves in Fabry's disease, and suggested that it could act as an endpoint to monitor nerve damage and the efficacy of enzyme replacement therapy . We have recently undertaken a more detailed study in patients with Fabry's disease and showed that the total Mainz severity score index – a validated measure of disease severity – correlated with corneal nerve fibre density, length and corneal endothelial cell density and area …”
Section: Corneal Confocal Microscope In Other Peripheral Neuropathiesmentioning
confidence: 99%